Dentipellicula guyanensis sp. nov. (Hericiaceae, Basidiomycota) from French Guiana - Zhou, Meng; Chen, Jia-Jia; Vlasák, Josef; Yuan, Yuan (Phytotaxa, 2021)
Dentipellicula guyanensis, a new species of Hericiaceae, is described and illustrated based on morphological characters and supported by molecular phylogenetic analyses using ITS and nLSU rDNA sequences. D. guyanensis is characterized by an annual and resupinate growth habit, a monomitic hyphal structure with non-amyloid, non-dextrinoid and acyanophilous generative hyphae, the presence of gloeoplerous hyphae in hymenophoral trama, the presence of gloeocystidia, and rough basidiospores measuring as 2.8–3.1 × 1.9–2.1 µm. A key to accepted species of Dentipellicula is provided.